A case of personal fitness tracker-assisted diagnosis of scabies. Issue 1 (March 2018) - Baird, Daniel; Kalus, Andrea; Gardner, Jennifer M.
Abstract : Accelerometer-based personal fitness trackers are frequently used to record physical activity and sleep quality, and the sleep monitoring capabilities may allow accelerometry to aid in the diagnosis of disorders, which impact sleep, including dermatologic issues. We report a case of scabies in which data from a patient's accelerometer-based fitness tracker recording sleep disturbances over time aided in the diagnosis.